Molecular actions of sex hormones in the brain and their potential treatment use in anxiety disorders - Pillerová, Miriam; Borbélyová, Veronika; Pastorek, Michal; Riljak, Vladimír; Hodosy, Július; Frick, Karyn M.; Tóthová, L’ubomíra (Frontiers in Psychiatry, 2022)
Anxiety disorders are one of the most prevalent mood disorders that can lead to impaired quality of life. Current treatment of anxiety disorders has various adverse effects, safety concerns, or restricted efficacy, therefore novel therapeutic targets need to be studied. Sex steroid hormones (SSHs) play a crucial role in the formation of brain structures, including regions of the limbic system and prefrontal cortex during perinatal development. In the brain, SSHs have activational and organizational effects mediated by either intracellular or membrane G-protein coupled receptors. During perinatal developmental periods, the physiological concentrations of SSHs lead to the normal development of the brain; however, the early hormonal dysregulation could result in various anxiety disorders later in life. Sex differences in the prevalence of anxiety disorders suggest that SSHs might be implicated in their development. In this review, we discuss preclinical and clinical studies regarding the role of dysregulated SSHs signaling during early brain development that modify the risk for anxiety disorders in a sex-specific manner in adulthood. Moreover, our aim is to summarize potential molecular mechanisms by which the SSHs may affect anxiety disorders in preclinical research. Finally, the potential effects of SSHs in the treatment of anxiety disorders are discussed.